Local Cyclic Voltammetry of a Langmuir–Blodgett Film on Water - Urbanová, Veronika; Bartl, Tomáš; Vavrek, František; Pačes, Ondřej; Pospíšil, Lubomír; Michl, Josef (Langmuir, 2024)
An electrochemical Langmuir–Blodgett trough that permits an examination of local redox processes in a layer floating on the surface of water with a scanning tunneling microscopy-tip ultramicroelectrode has been constructed and tested on a layer of 1,1′-dicarbooctadecyloxyferrocene.